Study of selective deposition mechanism of cerium-based conversion coating on Rheo-HPDC aluminium-silicon alloys. (20th November 2017) - Eslami, Maryam; Fedel, Michele; Speranza, Giorgio; Deflorian, Flavio; Andersson, Nils-Eric; Zanella, Caterina
Graphical abstract: Abstract: Cerium-based conversion coatings were deposited on Rheo-High Pressure Die Cast (HPDC) Al-Si alloys by immersion in cerium nitrate aqueous solutions. Rheocast Al-Si alloys have a heterogeneous microstructure and present a challenge for the conversion treatment. Different parameters were studied to optimize the conversion coating, and NaCl or H2 O2 were also added to the solution to modify or accelerate the deposition process. The mechanism of the coating formation was studied by means of focused ion beam milling (FIB) assisted SEM. The results show that applying cerium-based conversion coating to Al-Si alloys, is possible and a preferential deposition is obtained due to the presence of iron-rich intermetallic particles inside the eutectic region. The formation mechanism of selectively deposited cerium-based conversion coating includes dissolution of aluminium matrix, selective dissolution of aluminium from the noble intermetallic particles, oxidation of iron from the intermetallic particles, and the deposition of cerium hydroxide/oxide layer. The results reveal that the improvement in corrosion resistance in the presence of selectively deposited cerium-based conversion coating is more significant compared to the homogenous coating deposited from the conversion solution containing H2 O2 .